Decentralization of Financing Management and Corruption Conflict in the Education Budget - Intan Maurissa; Masduki Ahmad (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to discuss the history, purpose, and reality of decentralization of financing management in local government, as well as analyze the conflict of corruption of education funds in Indonesia and formulate solutions. The method used is a literature study with descriptive analysis techniques. It describes the analysis of data evidence from official government websites and from the results of other parallel studies to find new discussions and experiences to formulate solutions that are much more relevant to the current bureaucracy. The results of this study explain that local government corruption cases after decentralization are the highest of other government agencies, and the source of funds that is the strongest possibility of this practice is the education sector. The education budget continues to soar every year, but the progress of educational development still needs to grow. With the political payback concept, the corruption chain is increasingly difficult to break. As time goes by, the barriers to education seem unchanged. In this case, the DPRD is required to oversee the process of distributing education funds from the central ministry to local governments, the mass media must be more transparent, and the need for anti-corruption education from an early age to form an attitude of responsibility and discipline, this anti-corruption education needs to be given repeatedly, especially for political contestants.